Fine Needle Biopsy Versus Core Needle Biopsy Combined With/Without Thyroglobulin or BRAF 600E Mutation Assessment for Detecting Cervical Nodal Metastasis of Papillary Thyroid Carcinoma - Zhang, Xiaojun; Zhang, Xu; Du, Wei; Dai, Liyuan; Luo, Ruihua; Fang, Qigen; Ge, Hong (Frontiers in Endocrinology, 2021)
Objectives: To analyze the diagnostic benefit of fine needle aspiration biopsy cytology (FNAB-C) and core needle biopsy tissue (CNB-T) with the addition of thyroglobulin (Tg) in the washout of the needle or BRAF V600E mutation assessment in assessing cervical lymph node metastasis (LNM) in papillary thyroid carcinoma. Materials and Methods: A total of 186 lymph nodes were punctured by fine or core needle. The diagnostic performance of FNAB-C and CNB-T with Tg in the washout or BRAF V600E mutation assessment was compared. Results: The optimal cutoff value of FNAB-Tg was 1.0 ng/ml, with an AUC of 0.976. The sensitivity and specificity of FNAB-C in predicting cervical LNM were 97.4% and 71.4%, respectively, and the addition of FNAB-Tg could contribute to a sensitivity of 100% and a specificity of 95%, but the introduction of BRAF V600E mutation assessment was associated with a decreased sensitivity of 96.3% and a decreased specificity of 50.0%. The FNAB-Tg level showed a comparable distribution in malignant lymph nodes with different TgAb statuses, serum TSH levels, and serum Tg levels. The sensitivity and specificity of CNB-T in predicting cervical LNM were 98.9% and 100%, respectively. The addition of CNB-Tg did not alter the diagnostic ability, but the introduction of BRAF V600E mutation assessment obtained the best performance, with a sensitivity of 100% and specificity of 100%. Conclusion: The sensitivity and specificity of FNAB-C could be increased if combined with FNAB-Tg. CNB-T alone could provide satisfactory diagnostic reliability.